KRYNAROZ (Criticism – Narration – Understanding – Change) – an Original Proposal for Engaged Andragogical Research - Nowak-Dziemianowicz, Mirosława; Radecka, Agata (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The article consists of two complementary and mutually supporting parts. Thefirst part (Part A) focuses on the original concept of engaged critical research, presenting itsargumentation and successive stages in the proposed sequence. The second part (Part B)presents an example of applying the method in andragogical research. The paramountgoal of the presented text is to justify the thesis that critical narrative research is not onlypossible but also cognitional for pedagogy/adult education.